Construcc ión y validación de una escala de valores sociomorales - Tavares, Marialva Rossi; Menin, Maria Suzana De Stefano [UNESP]; Bataglia, Patrícia Unger Raphael [UNESP]; Vinha, Telma Pileggi; Tognetta, Luciene Regina Paulino [UNESP]; Martins, Raul Aragão [UNESP]; Moro, Adriano (FapUNIFESP (SciELO), 2016)
This study aimed to construct and validate a socio-moral values scale to measure the presence and commitment to the values of justice, respect, solidarity and democratic coexistence of students and teachers in Basic Education in public and private schools in São Paulo (10, 011 participants). The methodology involved the development of stories with pro and con alternatives at three levels of social perspective, as well as the application of a questionnaire to the sample and data processing using the Item Response Theory model for polytomous items. As a result, the classification of participants in standards set by value is presented and some educational implications of the research are discussed.
Construction et validation d’une échelle de valeurs socio-morales
Construção e validação de uma escala de valores sociomorais
Keywords: Item response theory; Moral judgment; Moral values; Social values